WAQF AL-NUQŪD IN INDONESIA (In Law Perspective) - Ong Argo Victoria (Jurnal Pembaharuan Hukum, 2018)
This article aims to make an overview on the rule and significance of waqf al-nuqūd (cash waqf) in Indonesia as a new social tool to alleviate poverty. The author highlights that Cash waqf is introduced as a new concept of waqf to solve many social problems in Muslim society of Indonesia. The qualitative methodology is employed to analyze the issues and development of cash waqf in Indonesia. Findings indicate that the cash waqf has been legalized by both Islamic scholar and national law of Indonesia so that Muslims have a chance to maximize the utilization of their waqf through a well-organized endowment and waqf organization.